Belief and practices of traditional post partum care among a rural community in Penang Malaysia - Munirah, Hishamshah; Muhammad Sirri' Ammar, Ramzan; Abdul, Rashid; Wan Nur Hidayah, Wan Mustaffa; Raihanah, Haroon; Nur Baizura, Badaruddin (2010)
Introduction: In developing countries, 70% of new mothers do not receive postpartum care. In Malaysia there are a number of traditional postpartum practices commonly practiced by new mothers.Aim: To describe the beliefs and practices related to the traditional postpartum care among women who had given live births in a village in Penang, Malaysia. Methodology: A descriptive cross sectional study was conducted among 68 women residents of a village who had given live births. Besides the baseline demographic data, information was collected on the postpartum confinement period and the aspects of traditional postpartum care. The data was analysed using the SPSS version 18.0.Results: All the 68 eligible women responded. All of them were aware of and practised postpartum ‘pantang’. The mean perceived confinement period was 53 days. Most respondents practice the confinement period due to self-belief (86.8%), others due to convenience (4.4%) and family pressure (4.4%). Most women in this village were aware of and practiced the common postpartum regimens except for the encouragement of more food intake and the limitation of contact with others. Older women were more likely to consume or use traditional herbs (χ² = 9.468, 4, P = 0.050) and to restrict their water intake (χ² = 18.827, P < 0.001). Most of them claimed that they would repeat the same traditional postpartum care regimens in their subsequent pregnancies and would advise their children the importance of doing so despite the presence of complications.Conclusion: This study revealed a high awareness and practice of traditional postpartum care.